Induced mutations in tomato SlExp1 alter cell wall metabolism and delay fruit softening. (January 2016) - Minoia, Silvia; Boualem, Adnane; Marcel, Fabien; Troadec, Christelle; Quemener, Bernard; Cellini, Francesco; Petrozza, Angelo; Vigouroux, Jacqueline; Lahaye, Marc; Carriero, Filomena; Bendahmane, Abdelhafid
Highlights: TILLING mutants were isolated in SlExp1 gene. Slexp1-6_W211S and Slexp1-7_Q213Stop mutants affect the polysaccharide-binding site. Mutations in SlExp1 gene increase fruit firmness and enhance fruit shelf-life. Loss of SlExp1 activity modifies cell wall polysaccharide chemical composition. Abstract: Fruit ripening and softening are key traits for many fleshy fruit. Since cell walls play a key role in the softening process, expansins have been investigated to control fruit over ripening and deterioration. In tomato, expression of Expansin 1 gene, SlExp1, during fruit ripening was associated with fruit softening. To engineer tomato plants with long shelf life, we screened for mutant plants impaired in SlExp1 function. Characterization of two induced mutations, Slexp1-6_W211S, and Slexp1-7_Q213Stop, showed that SlExp1 loss of function leads to enhanced fruit firmness and delayed fruit ripening. Analysis of cell wall polysaccharide composition of Slexp1-7_Q213Stop mutant pointed out significant differences for uronic acid, neutral sugar and total sugar contents. Hemicelluloses chemistry analysis by endo-β-1, 4-d -glucanase hydrolysis and MALDI-TOF spectrometry revealed that xyloglucan structures were affected in the fruit pericarp of Slexp1-7_Q213Stop mutant. Altogether, these results demonstrated that SlExp1 loss of function mutants yield firmer and late ripening fruits through modification of hemicellulose structure. These SlExp1 mutants represent good tools for breeding long shelf life tomato lines with contrasted fruit texture as well as for the understanding of the cell wall polysaccharide assembly dynamics in fleshy fruits.